Desenvolvimento de massa tipo talharim adicionada de CMS desidratada de tilápia e tomate em pó - Santos Junior, Edilberto Cordeiro dos (2015)
Pasta is among the main foods with high carbohydrate content consumed by Brazilian population, an average per capita of 6.2 kg per year. Its consumption is proportional to the purchasing power of the population. Pasta can be developed with improved nutritional characteristics added with other ingredients such as mechanically deboned meat (MDM) from tilapia and tomato powder. MDM was prepared by washing cycles to remove fat and undesirable aromatic compounds; the drying step took place in an oven with forced air circulation for 8 hours at 65 ºC. After that, the dried MDM was ground and sieved to provide appropriate particle size. Eleven formulations of pasta type “talharim” were developed using surface response, with addition of up to 15% of MDM and 7.5% tomato powder, and the cooking characteristics such as swelling, loss of solids and cooking time were evaluated. The masses were characterized by physical, physico-chemical, thermogravimetry, calorimetry, microbiological and sensory. Trough statistical analyses were selected three formulations that showed the best results for those parameters. The selected formulations were: F2 (MDM =12.5% and Tomato powder = 2.5%), F3 (MDM = 7.5% and Tomato powder = 7.5%), F4 (MDM =12.5% and Tomato powder = 7.5%) to compare with the standard formulation F0 (MDM = 0% and Tomato powder = 0%). The results showed that the addition of MDM and tomato powder promoted the increase of pasta weight of up 220.17% and produced a volume increase of up to 234%. The cooking time ranged from 4.33 min to 9.23 min and loss solids from 0.011% to 0.86%. For the chemical composition, the following results were obtained: proteins ranged from 9.93% to 14.79%, fat ranged from 8.61% to 11.25%, ash ranged from 1.80% to 2.78%, moisture from 7.78% to 5.22% and carbohydrates from 71.74% to 64.52%. It was observed that with the increasing proportions of MDM and tomato powder in formulations there was an increase in acidity numbers and reducing sugars and a decrease in water activity. In relation to sensorial analysis, there was no significant difference among formulations with respect to the attributes color, flavor, texture and overall acceptance. It can be concluded that the addition of the tomato powder up 7.5% and MDM up to 12,5% into “talharim” dough is a good alternative to improve nutritional values of these foods without affecting its sensory and cooking characteristics.